Effect of A1 and N doping on structural and optical properties of sol-gel derived ZnO thin films - Chatpong Bangbai; Krisana Chongsri; Wisanu Pecharapa; Wicharn Techitdheera (Universiti Kebangsaan Malaysia, 2013)
In this work, the preparation of ZnO, N-doped ZnO (NZO), Al-doped ZnO (AZO) and Al, N-doped ZnO (ANZO) thin films by the sol-gel spin-coating method is reported. The structural properties and surface morphologies of films were characterized by X-ray diffraction (XRD) and field emission scanning electron microscope (FE-SEM). The optical properties of the films were interpreted from their transmission spectra using UV-VIS spectrophotometer. The XRD and SEM results disclosed that the crystallization quality and grain size of as-prepared films were highly influenced by N and Al doping. UV-VIS spectrophotometer results indicated that Al and N additives could significantly enhance the optical transparency and induce the blue-shift in optical bandgap of ZnO films.